A systematic review and meta-analysis of the prevalence of common mental disorders in people with non-communicable diseases in Bangladesh, India, and Pakistan - Uphoff, Eleonora P (J Glob Health, 2019)
BACKGROUND: The prevalence of mental and physical comorbidities is unknown in South Asia, as estimates of mental ill health in patients with non-communicable diseases (NCDs) have predominantly come from studies based in the United States, Europe and Australasia. This systematic review and meta-analysis summarises evidence and provides pooled estimates of the prevalence of common mental disorders in adults with non-communicable diseases in South Asia. METHODS: We included prevalence studies of depression and anxiety in adults with diabetes, cancer, cardiovascular disease, and chronic respiratory conditions in Bangladesh, India, and Pakistan, published from 1990 onwards in international and country-specific databases. RESULTS: Out of 96 included studies, 83 provided data for random effects meta-analyses. The pooled prevalence of depression was 44% (95% confidence interval (CI) = 26 to 62) for patients with COPD, 40% (95% CI = 34 to 45) for diabetes, 39% (95% CI = 23 to 56) for stroke, 38% (95% CI = 32 to 45) for hypertension, and 37% (95% CI = 30 to 45) for cancer. The pooled prevalence of anxiety based on 28 studies was 29% (95% CI = 22 to 36). Many quality issues were identified in a critical appraisal of included studies, mostly relating to the sampling frame and selection process, the description of the methods and basic data, and the description of non-responders. CONCLUSIONS: Depression and anxiety are prevalent and underdiagnosed in people with physical comorbidities in Bangladesh, India, and Pakistan.